Extending the supply chain: Integrating operations and marketing in the online grocery industry - Boyer, Kenneth K.; Hult, G. Tomas M. (Journal of Operations Management, 2005)
AbstractThis study reports results from case studies of four Internet‐ordering and home‐delivery grocers and 2440 of their customers. Each grocer follows a different operations strategy as determined by choice of where to fulfill customer orders (from existing stores or from a dedicated DC) and by choice of delivery method (direct to the customer's home/office or indirect via customer pickup or third‐party logistics provider). The survey data from customers are used to assess the degree of integration between marketing and operations and the relationship with customer behavioral intentions. The results indicate that eBusiness‐, product‐, and service‐quality, all have a significant direct effect on customer behavioral intentions to purchase again. There is limited support for technology as a moderating factor. Finally, the relationships between the predictor variables and customer behavioral intentions differ across grocers. This supports the idea that grocers utilizing different operational strategies should focus attention on different facets of their business and provides insight as to where efforts should be directed.